Operations research proceedings 2016 : selected papers of the annual International Conference of the German Operations Research Society (GOR), Helmut Schmidt University Hamburg, Germany, August 30 - September 2, 2016 /: selected papers of the annual International Conference of the German Operations Research Society (GOR), Helmut Schmidt University Hamburg, Germany, August 30 - September 2, 2016. ([2018]) - Unknown
No abstract available